Nephron sparing treatment for renal carcinoma - Demkow, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2005)
Introduction. The growing number of kidney cancer patients treated by nephron sparing methods can be explained by the improvement of surgical technique and diagnostic methods. Imaging of the abdomen organs using the non invasive methods and making the medical knowledge more common lead to increase number of the new diagnose tumor cases in small size, low stage and easy to removed by surgery. In the beginning of the 90’s the percentage of the randomly diagnosed asymptomatic kidney tumor cases was at the level of 10% and now reached the level of the 50%. Purpose. The aim of the study is assessment of the nephron sparing treatment methods in renal cancer patients. Material and methods. Medline computerized literature searches were performed to identify methods of the nephron sparing treatments in renal cancer patients (surgical procedure and laparoscopy and tumor removing using the radiofrequency ablation r and cryotherapy) as well as the factors influencing on the final treatment results. Conclusions. Nephron sparing treatment provides effective therapy in selective group of renal cancer patients. Atfter the end of the currently caring multicentre randomised trials could be possible to propose a new treatment standards in small size tumors patient cases randomly diagnosed.